IMPACT OF COMMUNITY-BASED SHEEP BREEDING PROGRAMME ON FARM’S PROFITABILITY AND LAMB MORTALITY: THE CASE OF THE AKKARAMAN BREED - S. Güngör; B. Bahadir (Journal of Animal and Plant Sciences, 2024)
This study aimed to evaluate the impact of Community-Based Sheep Breeding Program (CBSBP) on gross profit and lamb mortality by comparing participated farms and non-participated farms by focusing on the case of Akkaraman breed in Niğde province of Turkey. The primary data were collected from 108 sheep farms, 54 farms participated and 54 farms those did not participate in the sheep breeding program. According to average treatment effect results derived by utilizing propensity score matching method, if all farms would participate to CBSBP, each farm acquired 6209.13 Turkish Lira (1094.92 USD) more gross profit and would be 3.47% less lamb mortality rate in the farms. The study indicated that CBSBP provided significant economic benefit and welfare of animal. Hence, further supporting and scaling up of community-based small ruminant breeding programs appears to be one of the best solutions for improving livestock genetic resources of rural communities in developing countries. Accordingly, incentive mechanisms for participating in breeding programs should be more focused on small-scale family farms and especially the young people in the rural area.
Keywords: sheep farming; propensity score matching; counterfactual impact analysis; genetic improvement; profitability